Problems of determination of the performance indicators of the Russian federation state - Georgiyevich Müller, Shamil Rinatovich UossoupovDiana Rustеmovna Fatykhova, Valentin Vladimirovich Laptev, Dmitry (Opción, 2019)
The article discusses the main features of the Russian Federation state policy implementation in the field of physical culture and sports. The methodological basis of the research is the systemic and structural-functional approaches, logical and comparative methods. As a result, the absence of elaborated alternative action scenarios and options in adopted programs makes it impossible to respond flexibly and promptly change the content of state policy. In conclusion, the process of information collection and processing concerning the achievement of the values of indicators is usually not automated, which makes the process long and time-consuming.